Assessment of the suitability of an existing L360NB natural gas pipeline for hydrogen transport using the hollow specimen technique - Ahmed Hamed; Monika Beschliesser; Stefan Fink; Gregor Mori (Journal of Materials Research and Technology)
Evaluating the efficiency and suitability of the existing natural gas transport and storage infrastructure for hydrogen use is the main key to boost hydrogen implementation. In this research, hollow specimens made of an existing L360NB natural gas pipeline steel, including a girth weld, were investigated up to 1000 bar hydrogen. Slow strain rate and cyclic ripple load tests at different stress levels were performed. The fracture surfaces of slow strain rate tests showed a certain limited hydrogen embrittlement. Cyclic loads up to 7000 cycles at different stresses resulted in no rupture, even at stresses above yield strength. The severe testing conditions say for the applicability of L360 NB pipeline steel for hydrogen transport.